A Model for Analysing Effects of Urban Spatial Configuration on Aesthetic Perception - Nia, Hourakhsh Ahmad (Eastern Mediterranean University EMU, 2015)
This thesis addresses the relationship between the elements of urban spatial configuration and human perception in contemporary urban spaces to understand how particular elements of urban spatial configuration can effect on people’s aesthetic perception. By qualitative grounded study in this research it hypothesised that the procedure of aesthetic cognition has different meanings and characteristic based on the elements of urban space configuration in different urban contexts. In this regard, theories of aesthetic evaluation of urban environment and the methodology for assessing aesthetic quality of urban environment investigated to take out the indicators of urban aesthetic based on human perception process. Then the indicators organized based on the process of human cognition in psychology into four main stages which are a study on a) the elements of urban space configuration (micro or macro) b) different approaches in organization between the elements (static or dynamic) c) subjective characteristics of good organization (formal or symbolic) d) effects of this organization on human cognition which leads to hedonic value (human aesthetic response). The outcome of this study reveals that every single aesthetic responses to the urban spaces regarding to the environmental configuration which is the outcome of interrelationship between immediate states of involvement, contemplative feeling, and sensual desire. It also enhances the knowledge concerning the role of symbolic and formal meanings of urban space configurations on aesthetic understanding of the environment. The study also proposed a methodological proposal (which prepares opportunities to be applicable in different scales of urban design) to apply the suggested model in each and every context. iv Keywords: Urban spatial configuration, Aesthetic properties, Aesthetic cognition, Cognition process.

ÖZ: Bu çalışma, kentsel mekan örüntüsünü oluşturan elemanlar ile çağdaş kent mekanlarındaki insan algısı arasındaki ilişkinin irdelenmesi üzerine odaklanmıştır. Bu bağlamda, kentsel mekan örüntüsünü oluşturan elemanlar ve bu elemanların bir araya gelerek oluşturdukları mekan organizasyonlarının insanlarda oluşturdukları estetik algı üzerinden tartışılmaktadır. Nitel bir araştırma metodu olarak temellendirilmiş kuram bağlamında ele alınmış olan bu tezde, ana yaklaşım farklı kentsel bağlamlardaki mekansal kurguyu oluşturan elemanların etkisi ile estetik bilişsellik sürecinin farklı anlam ve nitelikte geliştiği hipotezi üzerinden ele alınmıştır. Bununla birlikte, kentsel çevrenin estetik mekan algısı, teori ile birlikte, kentsel mekanların estetik kalitesini değerlendirme yöntemleri göz önünde bulundurularak, insan algısı üzerinden kentsel estetik göstergelerin tanımlanmaya çalışılmıştır. Psikolojideki kullanıldığı şekli ile insan bilişi(kavrama) 4 aşama üzerinden ele alınıp, a-kentsel mekan kurgusunu oluşturan elemanları(mikro ve/makro), b-Elemanlar arasındaki ilişkinin farklı kurgusal yapısı (static/dinamik) c-iyi bir mekan kurgusunun öznel özellikleri (sembolik/formel) d-Bu organizasyonun hedonik değere yol açan insan bilişi üzerindeki etkisi olarak tarif edilmiştir. Bu araştırmada ortaya çıkan başlıca sonuç, mekansal örüntü üzerinden geliştirilen mekana yönelik her estetisel tepkinin, içselleştirilmiş etkileşim, derin hissiyat geliştirme ve duysal arzu etkileşim ile ortaya çıktığı yönündeki saptamadır. Bunun yanında, kentsel mekan kurgusunun sembolik ve formel anlamarının kentsel çevrenin estetik kavrayişi üzerindeki bilgiye katkıda bulunmuştur.Çalışma aynı zamanda, metodolojik bir önerme(farklı ölçeklerde uygulanabilir bir esnek çerçeve) geliştirerek, bundan sonraki çalışmalara yönelikde katkı sağlamaya çalışmıştır. Anahtar Kelimeler: Kentsel Mekan Örüntüsü, Estetik Özellikler, Estetik Biliş Süreci
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Assoc. Prof. Dr. Resmiye Alpar Atun.
Keywords: Architecture; Urban Planning-Aesthetics; City Planning; Urban spatial configuration; Aesthetic properties; Aesthetic cognition; Cognition process